THE OUTSTANDING SUCCESS OF GRAB AND IMPLICATIONS TO THE TRADITIONAL TAXI IN VIETNAM - Hieu Vo, Minh; Pham, Van Kien; Trung Ngo , Quang (International Journal of Psychosocial Rehabilitation, 2020)
Background: Recently, a new business model with Grab’s smartphone apps is growing stronger and more popular in Vietnam. The new service type brings its consumers benefits that traditional players cannot such as lower price, convenience, luxury, etc. This inherently has changed Vietnamese using the behavior of the Taxi service. Consequently, this modern service leads to rapid declines in the traditional taxi industry.The context and purpose of the study: For these reasons, this study concentrates on enquiring about factors which have affected and changed the Vietnamese consumer behavior in using taxi services in recent years. As a result, six factors are drawn from the given literature with six hypotheses being built in the research model.Methods: To achieve the research objective, this article applies the exploratory factor analysis (EFA) and multivariate linear regression to analyze the data collected from 280 participants who answered the survey questionnaires related to the use of Grab's taxi services.Results: The final findings show that Grab using the behavior of consumers in Vietnam is mostly affected by the value of prices, the attractiveness of personal vehicles, the influence of society and the experiences.Conclusions: Under the perspective of managers, clearly finding out the factors can helpfully bring them suggestions in building and creating appropriate business strategies and allocating key investment resources. Finally, this article figures out implications in order to improve the traditional taxi industry in Vietnam.